Constructing Humphry Davy's Biographical Image. (3rd July 2019) - James, Frank A. J. L.
Abstract : This paper, which is also a contribution to the somewhat understudied area of the history of biography, discusses a couple of short accounts of Humphry Davy's life and the three major biographies published in the years following his death. These were an "anti-biography" by John Ayrton Paris (1831) and two admiring biographies by Davy's younger brother John Davy (1836, 1858). By examining the processes surrounding their writing and publication, this study illustrates how Davy's biographical reputation was constructed, how his surviving manuscripts and related documents came to be collected and preserved and so help us understand the effects they continue to exert on Davy scholarship.